Audiovisual links in exogenous covert spatial orienting. - Spence, C; Driver, J (1997)
Subjects judged the elevation (up vs. down, regardless of laterality) of peripheral auditory or visual targets, following uninformative cues on either side with an intermediate elevation. Judgements were better for targets on either modality when preceded by an uninformative auditory cue on the side of the target. Experiment 2 ruled out nonattentional accounts for these spatial cuing effects. Experiment 3 found that visual cues affected elevation judgments for visual but not auditory targets. Experiment 4 confirmed that the effect on visual targets was attentional. In Experiment 5, visual cues produced spatial cuing when targets were always auditory, but saccades toward the cue may have been responsible. No such visual-to-auditory cuing effects were found in Experiment 6 when saccades were prevented, though they were present when eye movements were not monitored. These results suggest a one-way cross-modal dependence in exogenous covert orienting whereby audition influences vision, but not vice versa. Possible reasons for this asymmetry are discussed in terms of the representation of space within the brain.